(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
In this article, we will present a research on the tracing of pre-school students mental representations on the phenomenon of dissolution of solids in a liquid. Thirty-one children drawn out of four different kindergarten classes participate in this research. The main subject of this research was the listing and ranking of 5-6 year old childrens representations, when called to predict problems concerning the dissolution of a solid substance in two different liquids (water or oil). The approach was qualitative and the research was carried out based on personal interviews and childrens drawings. The results showed that a significant percentage of the subject sample does not detect differences between the dissolution of sugar in water or oil, that there are major differences when children draw or predict and that while in their drawings children seem to comprehend the preservation of sugar in the solution, in their predictions many of them view that sugar is not preserved.